Complete blood count parameters and lymphocyte-related ratios in patients with alcohol use disorder - Baykara, Sema; Kaya, Şüheda; Berk, Şule Şirin (Journal of Dependence, 2019)
Objective: The study aimed to determine complete blood count (CBC) parameters, lymphocyte-related ratios in alcohol use disorder (AUD) patients with heavy alcohol use.Method: The dependent group included 75 individuals with history of alcohol use for at least 10 years. CBC parameters were obtained by evaluating the required tests before alcohol detoxification was initiated. The control group included 75 healthy individuals.Results: Alcohol use was 6.04 ± 1.45 units/day and the mean duration of alcohol use was 27.62 ± 8.68 years. There were significant differences between the groups based on white blood cell (WBC), neutrophil count, percentage, monocyte count, percentage, neutrophil to lymphocyte ratio (NLR), monocyte to lymphocyte ratio (MLR), favoring the dependent group. There were significant differences between the groups based on lymphocyte percentage, eosinophil count, percentage, basophil percentage, RBC and eosinophil to lymphocyte ratio (ELR), favoring the control group.Conclusion: CBC can be used as a rapid and inexpensive examination in AUD patients with heavy alcohol consumption to obtain information about inflammatory processes. and immunological systems which may be useful in AUD diagnosis treatment and follow-up.
Keywords: Alcoholism; blood cell count; lymphocytes; ınflammation